A cerium-modified CuMgAl catalyst and its preparation method and application
By adopting microwave aging treatment and cerium modification methods in CuMgAl catalysts, the problem of degradation of performance of traditional Cu-based catalysts under high temperature and high pressure conditions is solved, and the scope of application of CeO2 doping is broadened, which significantly improves the catalytic performance of the catalyst and stability.
Patent Information
- Application Number
- CN202411641041.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Traditional Cu-based catalysts are prone to sintering and agglomeration of active sites under high temperature and high pressure conditions, resulting in a decrease in catalytic performance, and the doping amount of rare earth element CeO2 is difficult to control. Excessive amount will reduce the total surface area of the catalyst and affect the catalytic performance.
The cerium-modified CuMgAl catalyst was treated by microwave aging to improve the catalytic performance of the catalyst and broaden the range of doping CeO2 in the catalyst. The process includes mixing the CuMgAl catalyst with a CeO2 solution, calcining after microwave aging, filtration, washing and drying to obtain a cerium-modified CuMgAl catalyst.
Through microwave aging treatment, the adsorption and activation ability of the catalyst to CO2 and the activation efficiency of H2 are improved, which extends the scope of application of CeO2 doping and enhances the stability and catalytic performance of the catalyst.
Smart Images

Figure CN119140106B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a cerium-modified CuMgAl catalyst and a preparation method and application thereof. Background Art
[0002] In the chemical industry, CO2 hydrogenation to methanol technology is regarded as an effective way to reduce the concentration of CO2 in the atmosphere and produce methanol chemicals with high added value. However, the catalyst performance of this technology has always been one of the key factors restricting its industrial application. Rare earth elements (such as La, Ce and Y) as modifiers or catalyst carriers have shown significant potential in the field of CO2 hydrogenation to methanol. The introduction of rare earth elements can effectively regulate key parameters such as the surface acidity and alkalinity of the catalyst, the dispersion of the active phase, the specific surface area, and the metal-carrier interaction, thereby improving the catalyst's adsorption and activation performance for CO2, increasing product selectivity, and improving the stability of the catalyst.
[0003] For Cu-based catalysts, modification with rare earth elements can significantly increase the Cu dispersion and specific surface area, which is beneficial to the adsorption and activation of CO2 on the catalyst surface. 2+ The reduction of rare earth is beneficial to the activation of H2, thereby improving the catalytic performance. However, although some progress has been made in rare earth-modified Cu-based catalysts, there are still some problems. For example, traditional Cu-based catalysts are prone to sintering and active site agglomeration under high temperature and high pressure reaction conditions, resulting in a decrease in catalytic performance. In addition, the stability of the catalyst needs to be further improved to meet the needs of long-term industrial applications. Ce, as one of the rare earth elements, also shows excellent performance in modifying Cu-based catalysts. CeO2, as a carrier, can form a strong metal-carrier interaction with the metal in the Cu-based catalyst, and its own rich oxygen vacancies are beneficial to the adsorption and activation of CO2. However, in terms of Ce-modified Cu-based catalysts, doping with an appropriate amount of CeO2 is beneficial to increasing the specific surface area of Cu, and excessive CeO2 will reduce the total surface area of the catalyst, which is not conducive to improving the catalytic performance of the catalyst. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a cerium-modified CuMgAl catalyst. When Ce is doped in a CuMgAl catalyst, it is easy to be excessive, resulting in a decrease in the total surface area of the catalyst, which affects the improvement of the catalytic performance of the catalyst. The present invention adopts a microwave aging method in the preparation step of the cerium-modified CuMgAl catalyst, which not only improves the catalytic performance of the cerium-modified CuMgAl catalyst, but also broadens the doping amount of CeO2 in the CuMgAl catalyst.
[0005] On the one hand, the present invention relates to a method for preparing a cerium-modified CuMgAl catalyst, which comprises: adding an alkaline solution to a precursor solution containing a copper source, a magnesium source and an aluminum source to adjust the pH to 8 to 9, heating in a water bath, aging and calcining to obtain a CuMgAl catalyst;
[0006] The CuMgAl catalyst is mixed with a solution containing a cerium source, and then subjected to microwave aging, filtration, washing, drying, and calcination to obtain a cerium-modified CuMgAl catalyst.
[0007] Furthermore, in the preparation method of the cerium-modified CuMgAl catalyst provided by the present invention, the microwave aging conditions are: microwave power of 100 to 900 W, temperature of 60 to 80° C., and aging time of 6 to 8 h.
[0008] Furthermore, in the method for preparing the cerium-modified CuMgAl catalyst provided by the present invention, the base in the alkaline solution is an organic base and / or an inorganic base;
[0009] The organic base is selected from at least one of sodium methoxide, sodium ethoxide and sodium tert-butoxide;
[0010] The inorganic base is selected from at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0011] Furthermore, in the preparation method of the cerium-modified CuMgAl catalyst provided by the present invention, the base in the alkaline solution is an organic base and an inorganic base, and the molar ratio of the organic base to the inorganic base is 1:3-6.
[0012] Further, in the preparation method of the cerium-modified CuMgAl catalyst provided by the present invention, the copper source is a nitrate of Cu;
[0013] The magnesium source is Mg nitrate;
[0014] The aluminum source is Al nitrate;
[0015] The cerium source is Ce nitrate.
[0016] Furthermore, in the preparation method of the cerium-modified CuMgAl catalyst provided by the present invention, in the precursor solution containing the copper source, the magnesium source and the aluminum source, the molar concentrations of Cu, Mg and Al are independently 0.5 to 5 mol / L;
[0017] In the solution containing the cerium source, the molar concentration of Ce is 0.1-1.5 mol / L.
[0018] Furthermore, in the method for preparing the cerium-modified CuMgAl catalyst provided by the present invention, the molar concentration of the alkali in the alkaline solution is 0.1 to 3 mol / L.
[0019] On the other hand, the present invention relates to a cerium-modified CuMgAl catalyst, which is prepared by the preparation method of the cerium-modified CuMgAl catalyst.
[0020] Furthermore, in the cerium-modified CuMgAl catalyst provided by the present invention, the molar ratio of Cu, Mg, Al and Ce in the cerium-modified CuMgAl catalyst is 0.8-1.4:2.8-3.2:0.8-1.2:0.2-0.5.
[0021] On the other hand, the present invention relates to the use of the cerium-modified CuMgAl catalyst in the synthesis of methanol from carbon dioxide.
[0022] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0023] (1) The present invention effectively improves the catalytic performance of the catalyst by treating the cerium-modified CuMgAl catalyst by microwave aging. Microwave aging not only promotes the structural adjustment of the catalyst surface, but also enhances the interaction between CeO2 and the Cu-based catalyst, thereby improving the catalyst's ability to adsorb and activate CO2, as well as the activation efficiency of H2.
[0024] (2) When introducing CeO2 as a modifier into traditional Cu-based catalysts, there is a problem of difficulty in controlling the doping amount. Excessive CeO2 tends to reduce the total surface area of the catalyst, which is not conducive to improving the catalytic performance. However, the present invention successfully broadens the doping range of CeO2 in the CuMgAl catalyst through the microwave aging method, so that the catalyst can maintain a high catalytic activity even when the CeO2 content is high.
[0025] (3) The present invention adopts a combination of organic base and inorganic base as a precipitation method. Compared with using only inorganic base, the cerium-modified CuMgAl catalyst prepared by the present invention exhibits better catalytic performance in the CO2 hydrogenation to methanol reaction, and therefore has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is the morphology of the CuMgAl catalyst.
[0028] Figure 2 This is the morphology of the conventional cerium-modified CuMgAl catalyst.
[0029] Figure 3 The electron microscope images of cerium-modified CuMgAl catalysts prepared by different methods are shown in Figure 1. a is the CuMgAl catalyst modified with excess cerium prepared in Example 2; b is the preparation of the CuMgAl catalyst modified with cerium after microwave treatment prepared in Example 3; c is the CuMgAl catalyst modified with cerium after the organic base and inorganic base are combined and microwave treated in Example 6; d is the CuMgAl catalyst modified with cerium after the organic base and inorganic base are combined and microwave treated in Example 7; e is the CuMgAl catalyst modified with cerium after the organic base and inorganic base are combined and microwave treated in Example 8. DETAILED DESCRIPTION
[0030] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0031] Example 1: This example provides the preparation of a conventional cerium-modified CuMgAl catalyst.
[0032] (1) The CuMgAl catalyst was prepared by co-precipitation method.
[0033] A certain amount of copper nitrate, magnesium nitrate and aluminum nitrate were dissolved in 150 mL of distilled water, wherein the concentration of copper nitrate was 0.8 mol / L, the concentration of magnesium nitrate was 2.8 mol / L, and the concentration of aluminum nitrate was 0.8 mol / L. Subsequently, the solution was stirred at room temperature, and the pH value of the solution was adjusted to 9.0 by adding an alkaline solution (0.24 mol / L of NaOH and 0.1 mol / L of Na2CO3) to obtain a blue precipitate. The solution was aged at 60°C in a water bath for 8 h, then filtered and the precipitate was washed with deionized water to remove excess ions. The solution was dried in an oven at 80°C overnight, taken out and calcined at 500°C in a muffle furnace for 5 h to obtain the following: Figure 1 CuMgAl catalyst shown.
[0034] (2) Ce-modified CuMgAl catalyst
[0035] A certain amount of cerium nitrate and 150mL of distilled water were used to prepare an aqueous solution with a concentration of 0.2mol / L cerium nitrate. After adding the CuMgAl catalyst, the mixture was stirred vigorously at a speed of 1000r / min for 2h, and then an alkaline solution (0.24mol / L NaOH and 0.1mol / L Na2CO3) was added to adjust the pH value of the solution to 9.0. The mixture was heated in a water bath at 60°C for 8h, and then filtered and the precipitate was washed with deionized water to remove excess ions. The mixture was dried in an oven at 80°C overnight, and then taken out and calcined in a muffle furnace at 500°C for 5h to obtain the following: Figure 2 The Ce-modified CuMgAl catalyst is shown.
[0036] EDX characterization showed that the molar ratio of Cu, Mg, Al and Ce in the cerium-modified CuMgAl catalyst prepared in this example was 8.2:28.4:8.5:2.1.
[0037] Example 2: This example provides the preparation of CuMgAl catalyst modified with excess cerium.
[0038] A certain amount of cerium nitrate and 150 mL of distilled water were used to prepare an aqueous solution with a concentration of 0.3 mol / L cerium nitrate. After adding the CuMgAl catalyst prepared in Example 1, the mixture was vigorously stirred at a speed of 1000 r / min for 2 hours, and then an alkaline solution (0.24 mol / L NaOH and 0.1 mol / L Na2CO3) was added to adjust the pH value of the solution to 9.0. The mixture was heated in a water bath at 60°C for aging for 8 hours, then filtered and the precipitate was washed with deionized water to remove excess ions. After drying in an oven at 80°C overnight, it was taken out and calcined in a muffle furnace at 500°C for 5 hours to obtain a cerium-modified CuMgAl catalyst, the electron microscope image of which is shown as follows Figure 3 As shown in a in .
[0039] Depend on Figure 3 From a in the figure, we can see that the excess CeO2 as a carrier forms a strong metal-carrier interaction with the metal in the Cu-based catalyst, forming a "blockage" on the surface of the CuMgAl catalyst, which in turn reduces its total surface area and affects its catalytic performance.
[0040] EDX characterization showed that the molar ratio of Cu, Mg, Al and Ce in the cerium-modified CuMgAl catalyst prepared in this example was 8.1:28.6:8.4:3.2.
[0041] Example 3: This example provides the preparation of cerium-modified CuMgAl catalyst after microwave treatment.
[0042] A certain amount of cerium nitrate and 150 mL of distilled water were used to prepare an aqueous solution with a concentration of 0.3 mol / L cerium nitrate. After adding the CuMgAl catalyst prepared in Example 1, the mixture was vigorously stirred at a speed of 1000 r / min for 2 hours, and then an alkaline solution (0.24 mol / L NaOH and 0.1 mol / L Na2CO3) was added to adjust the pH value of the solution to 9.0. The mixture was heated at 60°C with a microwave power of 100 W for aging for 8 hours, and then filtered, and the precipitate was washed with deionized water to remove excess ions. After drying in an oven at 80°C overnight, it was taken out and calcined at 500°C in a muffle furnace for 5 hours to obtain a cerium-modified CuMgAl catalyst, and its electron microscope image is shown as follows Figure 3 As shown in b.
[0043] Depend on Figure 3 As shown in b, although the excess CeO2 as a carrier also forms a "blockage" on the surface of the CuMgAl catalyst, it changes the stone structure of the CuMgAl catalyst surface and effectively improves its catalytic performance.
[0044] EDX characterization showed that the molar ratio of Cu, Mg, Al and Ce in the cerium-modified CuMgAl catalyst prepared in this example was 8.1:28.3:8.2:3.5.
[0045] Example 4: This example provides the preparation of cerium-modified CuMgAl catalyst after microwave treatment.
[0046] (1) The CuMgAl catalyst was prepared by co-precipitation method.
[0047] A certain amount of copper nitrate, magnesium nitrate and aluminum nitrate were dissolved in 150 mL of distilled water, wherein the concentration of copper nitrate was 1 mol / L, the concentration of magnesium nitrate was 3 mol / L, and the concentration of aluminum nitrate was 1 mol / L. Subsequently, the solution was stirred at room temperature, and the pH value of the solution was adjusted to 8.0 by adding an alkaline solution (0.05 mol / L of NaOH and 0.05 mol / L of NaHCO3) to obtain a blue precipitate. The solution was aged at 60 ° C for 8 h in a water bath, then filtered and the precipitate was washed with deionized water to remove excess ions. The solution was dried in an oven at 80 ° C overnight, and then taken out and calcined at 500 ° C for 5 h in a muffle furnace to obtain a CuMgAl catalyst.
[0048] (2) Ce-modified CuMgAl catalyst
[0049] A certain amount of cerium nitrate and 150mL of distilled water were used to prepare an aqueous solution with a concentration of 0.2mol / L cerium nitrate. After adding the CuMgAl catalyst, the solution was vigorously stirred at a speed of 1000r / min for 2h, and then an alkaline solution (0.05mol / L NaOH and 0.05mol / L NaHCO3) was added to adjust the pH value of the solution to 9.0. The solution was heated at 70℃ for aging for 6h at a microwave power of 500W, and then filtered and the precipitate was washed with deionized water to remove excess ions. It was dried in an oven at 80℃ overnight, taken out and calcined at 500℃ in a muffle furnace for 5h to obtain a cerium-modified CuMgAl catalyst.
[0050] EDX characterization showed that the molar ratio of Cu, Mg, Al and Ce in the cerium-modified CuMgAl catalyst prepared in this example was 10.8:31.1:10.5:1.9.
[0051] Example 5: This example provides the preparation of cerium-modified CuMgAl catalyst after microwave treatment.
[0052] (1) The CuMgAl catalyst was prepared by co-precipitation method.
[0053] A certain amount of copper nitrate, magnesium nitrate and aluminum nitrate were dissolved in 150 mL of distilled water, wherein the concentration of copper nitrate was 1.4 mol / L, the concentration of magnesium nitrate was 3.2 mol / L, and the concentration of aluminum nitrate was 1.2 mol / L. Subsequently, the solution was stirred at room temperature, and the pH value of the solution was adjusted to 9.0 by adding an alkaline solution (3 mol / L of NaOH) to obtain a blue precipitate. The solution was aged at 60 ° C for 8 h in a water bath, then filtered, and the precipitate was washed with deionized water to remove excess ions. The solution was dried in an oven at 80 ° C overnight, and then taken out and calcined at 500 ° C for 5 h in a muffle furnace to obtain a CuMgAl catalyst.
[0054] (2) Ce-modified CuMgAl catalyst
[0055] A certain amount of cerium nitrate and 150mL of distilled water were used to prepare an aqueous solution with a concentration of 0.5mol / L cerium nitrate. After adding the CuMgAl catalyst, the solution was vigorously stirred at a speed of 1000r / min for 2h, and then an alkaline solution (3mol / L NaOH) was added to adjust the pH value of the solution to 9.0. The solution was heated at 80℃ for 7h at a microwave power of 900W, and then filtered and the precipitate was washed with deionized water to remove excess ions. The solution was dried in an oven at 80℃ overnight, and then taken out and calcined at 500℃ in a muffle furnace for 5h to obtain a cerium-modified CuMgAl catalyst.
[0056] EDX characterization showed that the molar ratio of Cu, Mg, Al and Ce in the cerium-modified CuMgAl catalyst prepared in this example was 14.2:33.1:12.3:4.8.
[0057] Example 6: This example provides the preparation of a cerium-modified CuMgAl catalyst after a composite of an organic base and an inorganic base and combined with microwave treatment.
[0058] This example is the same as Example 4, except that the alkaline solution (0.05 mol / L NaOH and 0.05 mol / L NaHCO3) used in preparing the CuMgAl catalyst and the cerium-modified CuMgAl catalyst is replaced with an alkaline solution (0.025 mol / L sodium methoxide and 0.075 mol / L Na2CO3). The electron microscope image is as follows: Figure 3 As shown in c.
[0059] Example 7: This example provides the preparation of a cerium-modified CuMgAl catalyst after a composite of an organic base and an inorganic base and combined with microwave treatment.
[0060] This example is the same as Example 3, except that the alkaline solution (0.24 mol / L NaOH and 0.1 mol / L Na2CO3) used in preparing the CuMgAl catalyst and the cerium-modified CuMgAl catalyst is replaced with an alkaline solution (0.024 mol / L sodium ethoxide and 0.1 mol / L NaHCO3). The electron microscope image is as follows: Figure 3 As shown in d.
[0061] Example 8: This example provides the preparation of a cerium-modified CuMgAl catalyst after a composite of an organic base and an inorganic base and combined with microwave treatment.
[0062] This example is the same as Example 5, except that the alkaline solution (3 mol / L NaOH) used in preparing the CuMgAl catalyst and the cerium-modified CuMgAl catalyst is replaced with an alkaline solution (0.45 mol / L sodium tert-butoxide and 2.7 mol / L NaOH). The electron microscope image is as follows: Figure 3 As shown in e.
[0063] It can be seen from Examples 6 to 8 that as the concentration of the cerium source solution increases, the stone structure on the surface changes more and more, indicating that the combination of organic base and inorganic base is beneficial to the change of the stone structure on the surface of the CuMgAl catalyst modified by cerium.
[0064] Test Example: This test example provides an activity test of the catalyst prepared in each embodiment.
[0065] The reaction evaluation of the catalyst is carried out on a hydrogenation micro-reactor, and the size of the reaction tube is 12mm×500mm. The quartz sand and the catalyst are sieved into 20-40 meshes, the catalyst loading amount is 0.5g, the catalyst is loaded in the middle of the reaction tube, and the two ends are filled with quartz sand. The catalyst and quartz sand are packed tightly so that the catalyst can be fully utilized and evenly heated. Inert ceramic balls are used to line the bottom of the reaction tube to prevent quartz sand from clogging the reaction pipeline. After the reaction tube is loaded into the heating furnace, the air tightness of the entire device is checked, and it can be put into the reaction test when it is good. First, N2 with a flow rate of 30mL / min is passed through for 20min, then the heating is turned on to raise the temperature of the device to 300℃, and then H2 with a flow rate of 50mL / min is passed through for catalyst reduction for 2h. Subsequently, the device was cooled to 200°C under N2 atmosphere, N2 was switched to a mixed gas (the volume ratio of CO2:H2:N2 was 24:72:4), the pressure was increased to 2.5MPa, the air velocity was adjusted to 9000mL / (g·h), and then the CO2 hydrogenation to methanol catalytic reaction was carried out, and sampling and analysis were performed after the reaction was run for 4 hours. The reaction temperature was set at 200°C, 220°C, 240°C, 260°C, and 280°C, and each temperature point was continuously operated for 2 hours. To prevent condensation of gas phase products, the pipeline from the reactor outlet to the gas chromatograph needs to be insulated with a 110°C heating belt. The test results are shown in Table 1.
[0066] Table 1: Catalyst performance test results
[0067]
[0068] As shown in Table 1, the cerium-modified CuMgAl catalyst (Example 1) has improved CO2 conversion, methanol selectivity and methanol space-time yield compared to the unmodified CuMgAl catalyst (CuMgAl catalyst prepared in Example 1), indicating that cerium modification can effectively improve the performance of the catalyst. However, when the amount of cerium modification is excessive (Example 2), the performance of the catalyst decreases instead, which may be due to the "blocking" formed by excessive CeO2 on the catalyst surface, reducing the total surface area of the catalyst. It is worth noting that when the modified catalyst is treated with microwaves (Examples 3-5), the performance of the catalyst is further improved, especially the methanol selectivity and methanol space-time yield are significantly improved, because microwave treatment changes the stone structure on the catalyst surface, which is conducive to the catalytic reaction. In addition, with the increase in the concentration of the cerium source solution, combined with the use of organic bases and inorganic bases and microwave treatment (Examples 6-8), the performance of the catalyst shows an upward trend, among which the catalysts of Examples 7 and 8 show the best performance in CO2 conversion, methanol selectivity and methanol space-time yield, which further confirms the positive effect of the combination of organic bases and inorganic bases and microwave treatment on the improvement of catalyst performance. In summary, the microwave treatment provided by the present invention is conducive to improving the adverse effects of excessive cerium modification on the catalyst, and the performance of the cerium-modified CuMgAl catalyst is improved by the combined use of organic base and inorganic base.
[0069] The embodiments described above are part of the embodiments of the present invention, but not all of them. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.
Claims
1. A method for preparing a cerium-modified CuMgAl catalyst, characterized in that: include: Adding an alkaline solution to a precursor solution containing a copper source, a magnesium source and an aluminum source to adjust the pH to 8-9, heating in a water bath, aging and calcining to obtain a CuMgAl catalyst; The CuMgAl catalyst is mixed with a solution containing a cerium source, and then subjected to microwave aging, filtration, washing and drying, and then calcined to obtain a cerium-modified CuMgAl catalyst; The microwave aging conditions are as follows: microwave power is 100-900W, temperature is 60-80°C, and aging time is 6-8h; The alkali in the alkaline solution is an organic alkali and an inorganic alkali, and the molar ratio of the organic alkali to the inorganic alkali is 1:3-6; The organic base is selected from at least one of sodium methoxide, sodium ethoxide and sodium tert-butoxide; The inorganic base is selected from at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
2. The method for preparing the cerium-modified CuMgAl catalyst according to claim 1, characterized in that: The copper source is Cu nitrate; The magnesium source is Mg nitrate; The aluminum source is Al nitrate; The cerium source is Ce nitrate.
3. The method for preparing the cerium-modified CuMgAl catalyst according to claim 1, characterized in that: In the precursor solution containing the copper source, the magnesium source and the aluminum source, the molar concentrations of Cu, Mg and Al are independently 0.5 to 5 mol / L; In the solution containing the cerium source, the molar concentration of Ce is 0.1-1.5 mol / L.
4. The method for preparing the cerium-modified CuMgAl catalyst according to claim 1, characterized in that: The molar concentration of the alkali in the alkaline solution is 0.1 to 3 mol / L.
5. A cerium-modified CuMgAl catalyst, characterized in that: The catalyst is prepared by the method for preparing the cerium-modified CuMgAl catalyst according to any one of claims 1 to 4.
6. The cerium-modified CuMgAl catalyst according to claim 5, characterized in that The molar ratio of Cu, Mg, Al and Ce in the cerium-modified CuMgAl catalyst is 0.8-1.4:2.8-3.2:0.8-1.2:0.2-0.
5.
7. Use of the cerium-modified CuMgAl catalyst according to claim 5 in synthesizing methanol from carbon dioxide.
Citation Information
Cited By
Copper-magnesium-aluminum hydrotalcite catalyst for synthesizing tetra-tert-butyl biphenyl diquinone through oxidative coupling of 2, 6-di-tert-butyl phenol and preparation method of copper-magnesium-aluminum hydrotalcite catalyst
CN120900635A